VESTIBULITIS - Elfahmi, Elfahmi; Jenny Tri Yuspita Sari (Yayasan Nusantara Hasana Berdikari, 2025)
Vestibulitis is an inflammatory condition affecting the vestibular area, commonly referring to inflammation of the vulvar vestibule or the nasal vestibule, depending on the anatomical context. The condition is characterized by localized pain, erythema, tenderness, and discomfort, which may significantly affect a patient’s quality of life. Vulvar vestibulitis, often associated with vulvodynia, presents with pain during touch, sexual intercourse, or tampon insertion, while nasal vestibulitis is commonly caused by bacterial infection, particularly Staphylococcus aureus, and manifests as pain, crusting, and erythema around the nasal opening. The diagnosis of vestibulitis is primarily clinical, supported by patient history and physical examination. Management depends on the underlying cause and severity of symptoms and may include topical or systemic antibiotics, anti-inflammatory agents, local anesthetics, and supportive measures. Early diagnosis and appropriate treatment are essential to relieve symptoms, prevent complications, and improve patient outcomes.